Taking cover: Human capital accumulation in the presence of shocks and health insurance - Paulino Font-Gilabert (University of Essex, Institute for Social and Economic Research (ISER), 2020)
Using the expansion of a large-scale health insurance program in Mexico and variation in local rainfall levels, I estimate whether the program-induced increase in healthcare coverage protected the educational attainment of primary school children in the event of adverse climatic shocks. Results show that the universalization of healthcare mitigated the negative effect of atypical rainfall on test scores, particularly in more marginalized and rural areas. An analysis of the mechanisms at play shows a reduced incidence of sickness among children, lower demand for their time, and higher stability in household consumption among program-eligible families exposed to rainfall shocks.
Keywords: I13; I15; I25; O12; 330; climate resilience; academic achievement; health insurance; Seguro Popular; Mexico